Proteomic analysis of deglycosylated Proteins in normal human serum using anhydrous hydrogen fluoride treatment - Sriyam Supawadee (2018)
Deglycosylation with anhydrous hydrogen fluoride (HF) is an alternative method for removing oligosaccharides from glycoproteins which can be extremely useful for identification of proteins and the biological roles of post-translational modifications. In this study, a glycosylated proteome of human serum was treated by anhydrous HF to deglycosylate the number of oligosaccharides from glycoproteins which facilitated protein identification using proteomic analysis. In the preliminary result, the high performance liquid chromatography (HPLC) and liquid chromatography mass spectrometry (LC-MS) showed that there was no cleavage of disulfide bonds in HF-treated insulin as a negative control. The effect of HF deglycosylation on electrophoresis pattern was studied by resolving on one-dimensional (1-D) and two-dimensional (2-D) gels. Deglycosylation of glycoproteins in human serum resulted in different protein patterns on 1-DE and 2-DE gels with the clearer protein patterns and low amount of complexity. The deglycosylated serum proteins could be enriched and identified by MS analysis. Using this approach, it indicated that the proteins in human serum have some glycosylation that affected to the protein analysis and might possess the diverse biological functions. Therefore, this deglycosylation technique is an effective method to solve the problem of oligosaccharide interference in proteome analysis and be able to use for further glycan analysis.